Evaluation of Functional NK Cell Responses in Vaccinated and SIV-Infected Rhesus Macaques - Vargas-Inchaustegui, Diego A.; Ying, Olivia; Demberg, Thorsten; Robert-Guroff, Marjorie (Frontiers in Immunology, 2016)
NK cells are crucial components of the innate immune system due to their capacity to exert rapid cytotoxic and immunomodulatory function in the absence of prior sensitization. NK cells can become activated by exposure to target cells and/or by cytokines produced by antigen-presenting cells. In this study, we examined the effects of a simian immunodeficiency virus (SIV) vaccine regimen and subsequent SIV infection on the cytotoxic and immunomodulatory functions of circulatory NK cells. While vaccination did not significantly impact the capacity of NK cells to kill MHC-devoid 721.221 target cells, SIV-infection led to a significant decrease in target cell killing. NK cells from un-infected macaques were responsive to a low dose (5 ng/ml) of IL-15 pre-activation, leading to significant increases in their cytotoxic potential, however, NK cells from SIV-infected macaques required a higher dose (50 ng/ml) of IL-15 pre-activation in order to significantly increase their cytotoxic potential. In contrast, no differences were observed in the capacity of NK cells from vaccinated and SIV-infected macaques to respond to IL-12 and IL-18. Similarly, NK cells both before and after infection exhibited equivalent responses to Fc-mediated activation. Collectively our results show that early SIV-infection impairs the natural cytotoxic capacity of circulatory NK cells without affecting Fc-mediated or cytokine-producing function.